Chloroplast Calcium Signaling in the Spotlight - Navazio, Lorella; Formentin, Elide; Cendron, Laura; Szabò, Ildikò (Frontiers in Plant Science, 2020)
Calcium has long been known to regulate the metabolism of chloroplasts, concerning both light and carbon reactions of photosynthesis, as well as additional non photosynthesis-related processes. In addition to undergo Ca2+ regulation, chloroplasts can also influence the overall Ca2+ signalling pathways of the plant cell. Compelling evidence indicate that chloroplasts can generate specific stromal Ca2+ signals and contribute to the fine tuning of cytoplasmic Ca2+ signalling in response to different environmental stimuli. The recent set up of a toolkit of genetically encoded Ca2+ indicators, targeted to different chloroplast subcompartments (envelope, stroma, thylakoids) has helped to unravel the participation of chloroplasts in intracellular Ca2+ handling in resting conditions and during signal transduction. Intra-chloroplast Ca2+ signals have been demonstrated to occur in response to specific environmental stimuli, suggesting a role for these plant-unique organelles in transducing Ca2+-mediated stress signals. In this mini-review we present current knowledge of stimulus-specific intra-chloroplast Ca2+ transients, as well as recent advances in the identification and characterization of Ca2+-permeable channels/transporters localized at chloroplast membranes. In particular, the potential role played by cMCU, a chloroplast-localized member of the mitochondrial calcium uniporter (MCU) family, as component of plant environmental sensing is discussed more in detail, taking into account also some specific structural features of cMCU. In summary, the recent molecular identification of some players of chloroplast Ca2+ signalling has opened new avenues in this rapidly developing field and will hopefully allow a deeper understanding of the role of chloroplasts in shaping physiological responses in plants.